Antioxidant Activity of Jojoba (Simmondsia chinensis) Seed Residue Extract - Arnold Patogi Siahaan; Eti Rohaeti; Ali Mahmoud Muddathir; Irmanida Batubara (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Jojoba (Simmondsia chinensis (Link)) is a shrub plant that widely used as cosmetic ingredients especially jojoba oil. When making jojoba oil, the residue still reminds and become waste. This study aimed to determine the antioxidant activity of jojoba seed residue (JSR). Jojoba seed residue was collected from Sudan. The JSR extracted by maceration with n-hexane, ethyl acetate, and 70% ethanol solvent. The antioxidant activity was determined using DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The result showed that 70% ethanol extract of JSR had the highest antioxidant activity with 50% Inhibition Concentration (IC50) value of 219.42 mg/L. The 70% ethanol extract was fractionated by using silica gel column chromatography with gradient elution produced 10 fractions. All fractions showed antioxidant activity (IC50106-447 mg/L). Fraction 3 had the highest antioxidant activity with IC50 value of 106.26 mg/L. Therefore, JSR has a great potential for use as a raw material in cosmetic and pharmaceutical products industry, or as a source of bioactive compounds.